Secretory structures and essential oil composition in Stachys officinalis (L.) Trevisan subsp. officinalis (Lamiaceae) from Italy. Issue 9 (3rd May 2017) - Giuliani, Claudia; Pellegrino, Roberto Maria; Selvaggi, Roberta; Tani, Corrado; Tirillini, Bruno; Maleci Bini, Laura
Abstract: The secretory structures and the volatile fraction of Stachys officinalis (L.) Trevisan subsp. officinalis (Lamiaceae) from Italy were studied for the first time. Peltate and small capitate trichomes were observed on the whole plant (leaves and inflorescences). In the peltate trichomes, an unusual polyphenols content was evidenced by the histochemical methods. The volatile fraction was obtained by a solvent extract from the distillation water of leaves and inflorescences and analysed by GC-MS. Forty-four constituents for leaves, representing 94.1% of the total volatiles, and 57 compounds for flowers, accounting for 90.1% of the total volatiles, were identified. ( E )-caryophyllene (20.1%), ( E )-nerolidol (14.3%), caryophyllene oxide (6.1%) and γ-cadinene (5.7%) were recognised as the main constituents for the leaf volatile fraction, while caryophyllene oxide (16.5%), ( E )-nerolidol (15.4%), humulene epoxide II (9.2%) and α-pinene (7.0%) were the main compounds for the flower volatile fraction. Abstract :